2020
DOI: 10.1002/mabi.202000161
|View full text |Cite
|
Sign up to set email alerts
|

Bone Morphogenetic Protein‐2‐Activated 3D‐Printed Polylactic Acid Scaffolds to Promote Bone Regrowth and Repair

Abstract: Uneven distribution of pores, lack of connection between holes, low reproducibility, insufficient mechanical strength, and incomplete volatility of organic solvents are some problems associated with traditional tissue engineering methods for bone defect repair. These characteristics reduce the quality and stability of products. This study uses 3D printing (3DP) to fabricate a biocompatible poly(lactic) acid‐based scaffold for repairing bone tissue. Hence, three different types of scaffolds are assessed: a free… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…One of the most important and investigated groups of synthetic biodegradable polymers are polyesters that can decompose after fulfilling their purpose as bone healing biomaterials, resulting in natural nontoxic by-products. Some examples of these polymers are polylactic acid (PLA), [59] poly(glycolic acid) (PGA), poly(llactic acid) (PLLA), PCL, poly(d,l-lactide-co-glycolide) (PLGA) copolymers, [60] which have a relatively hydrophobic nature (Figure 1b-f).…”
Section: Polyestersmentioning
confidence: 99%
“…One of the most important and investigated groups of synthetic biodegradable polymers are polyesters that can decompose after fulfilling their purpose as bone healing biomaterials, resulting in natural nontoxic by-products. Some examples of these polymers are polylactic acid (PLA), [59] poly(glycolic acid) (PGA), poly(llactic acid) (PLLA), PCL, poly(d,l-lactide-co-glycolide) (PLGA) copolymers, [60] which have a relatively hydrophobic nature (Figure 1b-f).…”
Section: Polyestersmentioning
confidence: 99%
“…The quinone/semiquinone formed by the catechol group on the PDA layer results in irreversible covalent conjugation between biomolecules and the surface of organic substitutes using similar Michael addition and Schiff formation reactions (Lee et al, 2007). Yao et al (2020) found that bone cell differentiation and bone regeneration were enhanced in 3Dprinted polylactic acid scaffolds with PDA modification and BMP-2 immobilization. PELA electrospun fibers immobilized with BMP-2 mediated by PDA showed better induction of differentiation into cartilage and bone in an acetabulum defect porcine model compared to the autotendon or PDA-coated PELA electrospun fibers groups (Wu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, certain drawbacks, including difficult storage as well as uncontrolled delivery of growth factors, potential adverse effects in vivo , and laser modification ( Li et al, 2017 ) may even impair the mechanical properties of artificial ligaments itself, hampering the application of these methods. Bone morphogenetic protein-2 (BMP-2), one of the transforming growth factors (TGFs), plays an important role in the initial stage of bone formation ( Yao et al, 2020 ) and tissue regeneration ( Poon et al, 2016 ). BMP-2 could promote the proliferation and osteogenic differentiation of bone mesenchymal stem cells (BMSCs) ( Bayat et al, 2017 ; Yao et al, 2020 ) and stimulate the maturation of pre-osteoblast, consequently enhancing the secretion of bone-associated protein and mineralization ( Zhang et al, 2017 ), and it is involved in bone metabolism as well ( Rawadi et al, 2003 ; Chen et al, 2004 ; Cao and Chen, 2005 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During an orthodontic treatment, the balance between bone formation and bone resorption is a critical issue that needs to be addressed. [1,2] Bone remodeling is a complex multi-step process involving the coordinated action of osteoblasts (OBs) and osteoclasts (OCs). [3][4][5][6] OBs are the only of human osteoblast-like cells MG63 and rat bone mesenchymal stem cells (rBMSCs).…”
Section: Introductionmentioning
confidence: 99%